MODEL PERTUMBUHAN LOGISTIK PREDATOR DAN PREY PADA POPULASI PREY DAN SOLUSI KESETIMBANGAN - Sunarsih, Sunarsih; Hidayati, Firsty Nur (JURNAL SAINS DAN MATEMATIKA, 2010)
ABTRACT-- A  predator-prey model with logistic growth in the prey population is an iknteraction between  a  predator and  a  prey  population with logistic  growth  in the  prey  population. The  equations  in this model  are  non  linear dffirentiat  equation  with two dependent  variables.  In this  system,  H(t)  X size  of  prey population at time t  and P(t) is size  of  predator  population  at time t . This  model  have  three  equilibria.Key words  : logistic,  predator and  prey, equilibrium  pointPermalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3118